Analisa Perbandingan Efisiensi Daya Dan Kapasitas Pendinginan Antara AC Central Dan AC Split Pada Kereta Ekonomi - Puspitasari, Mariana Diah (Politeknik Perkeretaapian Indonesia Madiun, 2018)
PT KAI (Persero) has never stopped transforming itself. His transformation was highly considered when PT KAI (Persero) was under the authority of Jonan Ignasius. Edi Sukmoro then continued the transformation. Some improvements in service quality at each train station require appreciation from various aspects. At present, security is improved, tickets are easier to obtain, and travel is more convenient because trains are provided by AC. However, given the costs involved, installation of air conditioners in all business and economy class cars does not apply central air conditioning but divides air conditioning as applied in the home or office. This research is to find out the most efficient air conditioning in consuming energy in trains, therefore, it is conducted. This study also investigates the most effective air conditioning in cooling. The results showed that the energy efficiency of split air coolers was lower than central air coolers. Regarding cooling capacity, central AC is produced by PT INKA which has a higher cooling capacity than split AC.